Effects of hyperbaric pressure on the oxidative stress status in healthy subjects - Phuong Minh Nguyen; Ben Huu Nguyen; Manh Van Phan; Hoan Duy Bui (Revista Cubana de Medicina Militar)
Introduction: In the hyperbaric pressure environment the partial pressure of each gas component increases, which increases oxygen partial pressure. This causes the generation of free radicals and oxidative stress. Objective: To determine the effects of hyperbaric pressure on the oxidative stress status in healthy subjects. Methods: 29 healthy men performed standardized hyperbaric chamber dive to a depth of 30 meters of water (msw) for 30 minutes. Blood samples were collected before compression, immediately after decompression and 1 hour after decompression. The levels of Malondialdehyde, Catalase and Superoxide Dismutase were measured in blood samples. Results: Malondialdehyde activity increased immediately after decompression and recovered at 1 hour after decompression. Superoxide Dismutase enzyme activity decreased immediately after decompression as well as 1 hour after decompression. Catalase enzyme activity increased immediately after decompression, which was significant at 1 hour after decompression. Conclusion: Changes in the biologic markers Malondialdehyde, Catalase and Superoxide Dismutase suggest the appearance of oxidative stress under the influence of a hyperbaric pressure environment.